2011
DOI: 10.1053/j.gastro.2011.01.033
|View full text |Cite
|
Sign up to set email alerts
|

GATA Factors Regulate Proliferation, Differentiation, and Gene Expression in Small Intestine of Mature Mice

Abstract: Background & Aims GATA transcription factors regulate genes in multiple organs to control proliferation and differentiation. GATA4 is expressed in the proximal 85% of the small intestine, where it regulates the expression of genes that are specifically expressed by absorptive enterocytes. GATA6 is co-expressed with GATA4 but is also expressed in the ileum; its function in the mature small intestine is unknown. Methods We investigated the function of GATA6 in small intestine using adult mice with inducible di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
136
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(155 citation statements)
references
References 43 publications
17
136
1
1
Order By: Relevance
“…Since GATA6 is highly expressed in the crypt compartment in the intestine 19 , it may also play an essential role in the regulation of Lgr5 expression in intestinal stem cells. Consistent with this notion, it has recently been reported that conditional deletion of GATA6 in intestinal epithelium results in decreased proliferation of crypt progenitor cells and abnormal differentiation of secretary cells 26 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Since GATA6 is highly expressed in the crypt compartment in the intestine 19 , it may also play an essential role in the regulation of Lgr5 expression in intestinal stem cells. Consistent with this notion, it has recently been reported that conditional deletion of GATA6 in intestinal epithelium results in decreased proliferation of crypt progenitor cells and abnormal differentiation of secretary cells 26 .…”
Section: Discussionsupporting
confidence: 54%
“…GATA6 is a zinc finger transcription factor that is required for the proliferation, development and specific gene regulation of the gastrointestinal tract and other tissues [24][25][26] . GATA6 has also been reported to be involved in colorectal tumour invasion and in the conversion of Barrett metaplasia to adenocarcinoma 27,28 .…”
Section: Gata6 Upregulates Lgr5 Expression In Colorectal Cancer Cellsmentioning
confidence: 99%
“…4c,e), or with proximal vs . distal intestinal identity (known: Gata4 , Nr1h4 24 and novel: Creb3l3, Jund, Osr2, Nr1i3 ; Extended Data Fig. 4d).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that GATA4 or GATA6 is necessary for secretory progenitors to commit to a neuroendocrine lineage. [167][168][169] Immunohistochemical analysis of mouse small intestine revealed that GATA4 is only expressed in villus enterocytes. GATA5 was not detected in enterocytes, but it was detected in other lineages.…”
Section: Cell Differentiation and Intestinal Adaptationmentioning
confidence: 99%